Generation of stable cell line by using chitosan as gene delivery system - EKENTOK ATICI, CEYDA; ÖZBAŞ, SUNA (SPRINGER, 2016)
Establishing stable cell lines are useful tools to study the function of various genes and silence or induce the expression of a gene of interest. Nonviral gene transfer is generally preferred to generate stable cell lines in the manufacturing of recombinant proteins. In this study, we aimed to establish stable recombinant HEK-293 cell lines by transfection of chitosan complexes preparing with pDNA which contain LacZ and GFP genes. Chitosan which is a cationic polymer was used as gene delivery system. Stable HEK-293 cell lines were established by transfection of cells with complexes which were prepared with chitosan and pVitro-2 plasmid vector that contains neomycin drug resistance gene, beta gal and GFP genes. The transfection efficiency was shown with GFP expression in the cells using fluorescence microscopy. Beta gal protein expression in stable cells was examined by beta-galactosidase assay as enzymatically and X-gal staining method as histochemically. Full complexation was shown in the above of 1/1 ratio in the chitosan/pDNA complexes. The highest beta-galactosidase activity was obtained with transfection of chitosan complexes. Beta gal gene expression was 15.17 ng/ml in the stable cells generated by chitosan complexes. In addition, intensive blue color was observed depending on beta gal protein expression in the stable cell line with X-gal staining. We established a stable HEK-293 cell line that can be used for recombinant protein production or gene expression studies by transfecting the gene of interest.
Keywords: Chitosan; Beta gal; pDNA; Stable cell; IN-VITRO; DNA; POLYETHYLENIMINE; TRANSFECTION